Review of Gerard Bouchard's Interculturalsm: A View From Quebec - McManus, Matthew; O'Callaghan, Connor (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
This is a review of Professor Bouchard's new text promoting interculturalism as the most adequate cultural policy for Quebec, and defending it against competitors.